Effect of thunderstorms and airborne grass pollen on the incidence of acute asthma in England, 1990-94. Issue 8 (August 1997) - Newson, R; Strachan, D; Archibald, E; Emberlin, J; Hardaker, P; Collier, C
Abstract : BACKGROUND: Thunderstorms and prior grass pollen counts were investigated as predictors of daily hospital admissions for asthma in England. This study was motivated by reports in the literature of spectacular asthma epidemics associated with thunderstorms, particularly in the grass pollen season. METHODS: Asthma admissions for two age groups (0-14 years and 15 and over) were measured using the Hospital Episodes System (HES) in the 14 regional health authorities (RHAs) in England. Thunderstorms were measured daily in each RHA using densities of sferics (lightning flashes). Relative asthma excesses for moderate positive and exceptionally high sferic densities, with or without previous high grass pollen counts, were measured using log linear autoregression–allowing for weekly, seasonal, and longer term background variation–and pooled over RHAs by calculating geometric means. RESULTS: Relative risks from all RHAs were pooled to form geometric means. Exceptional sferic densities were associated with a relative excess risk of around 25% in both age groups. Moderate sferic densities were associated with a smaller excess, statistically significant in the two age groups taken together. In five RHAs in which grass pollen counts were available, high pollen counts for the previous five days were associated with an amplification of the excess associated with thunderstorms. CONCLUSION: Very large sferic densities are associated with moderate rises in hospital admissions for acute asthma. However, typical thunderstorm days are not associated with spectacular asthma epidemics of the scale previously reported in the literature. Thunderstorm-associated excesses are amplified after a run of high pollen counts.